Computational Intelligence International Joint Conference, IJCCI 2012 Barcelona, Spain, October 5-7, 2012 Revised Selected Papers - Madani, Kurosh; Correia, António Dourado; Rosa, Agostinho; Filipe, Joaquim (Studies in Computational Intelligence, 2015)
The present book includes extended and revised versions of a set of selected papers from the Fourth International Joint Conference on Computational Intelligence (IJCCI 2012)., held in Barcelona, Spain, from 5 to 7 October, 2012. The conference was sponsored by the Institute for Systems and Technologies of Information, Control and Communication (INSTICC) and was organized in cooperation with the Association for the Advancement of Artificial Intelligence (AAAI). The conference brought together researchers, engineers and practitioners in computational technologies, especially those related to the areas of fuzzy computation, evolutionary computation and neural computation. It is composed of three co-located conferences, each one specialized in one of the aforementioned -knowledge areas. Namely: - International Conference on Evolutionary Computation Theory and Applications (ECTA) - International Conference on Fuzzy Computation Theory and Applications (FCTA) - International Conference on Neural Computation Theory and Applications (NCTA) Recent progresses in scientific developments and applications in these three areas are reported in this book This book includes revised and extended versions of a strict selection of the best papers presented at the conference. .